2014
DOI: 10.5664/jcsm.3786
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Positive Air Pressure (CPAP) on Nightmares in Patients with Posttraumatic Stress Disorder (PTSD) and Obstructive Sleep Apnea (OSA)

Abstract: In Veterans with PTSD and OSA, CPAP therapy reduces PTSD-associated nightmares and improves overall PTSD symptoms. We recommend that all PTSD patients should be screened clinically for symptoms of OSA and receive CPAP treatment whenever possible to improve PTSD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Regarding treatment, one ongoing study in a small sample of PTSD patients with SDB is prospectively comparing two groups: one using only standard cognitive-behavioral therapy with prolonged exposure versus combination treatment comprising both exposure and an auto-adjusting positive airway pressure device; the preliminary data suggest more benefit in the latter group [93]. A retrospective study recently published demonstrated a marked decrease in nightmares among PTSD patients using CPAP therapy for OSA [94]. Additional investigations could test the impact of PTSD treatment on sleep breathing problems as well as SDB treatment impact on PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment, one ongoing study in a small sample of PTSD patients with SDB is prospectively comparing two groups: one using only standard cognitive-behavioral therapy with prolonged exposure versus combination treatment comprising both exposure and an auto-adjusting positive airway pressure device; the preliminary data suggest more benefit in the latter group [93]. A retrospective study recently published demonstrated a marked decrease in nightmares among PTSD patients using CPAP therapy for OSA [94]. Additional investigations could test the impact of PTSD treatment on sleep breathing problems as well as SDB treatment impact on PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In PTSD patients, recurrent arousals might potentiate nighttime symptoms, such as recall of nightmares, an assertion supported by the finding that treatment of OSA with CPAP appears to reduce the frequency of nightmares in PTSD patients. 16 Poor sleep quality related to sleep apnea may also contribute to daytime PTSD symptoms of irritability, impairment in concentration, fatigue, as well as comorbid psychiatric conditions. Sleep apnea has been associated with worsened scores across a wide range of daytime and nighttime symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…8,40,41 In one of these studies involving 40 veterans with combat-related PTSD, a positive association was established between the reduction in PCL-M and the average of hours of CPAP use per night. 40 Similarly, Orr and colleagues 41 showed significant reduction in PTSD symptoms following 6 months of treatment with CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical investigations suggest that treatment of OSA in veterans with PTSD may improve the underlying psychological disturbances and reduce nightmares. 4,8,9 However, despite the overall improvement in PTSD symptomatology with CPAP therapy, adherence to treatment is far worse in these patients compared with the general population with OSA. 10,11 The reasons behind this poor adherence have not been thoroughly investigated but anxiety disorder, nightmares, claustrophobia, and comorbid insomnia have been implicated in low CPAP usage.…”
Section: Introductionmentioning
confidence: 99%